Impairment of motor planning in patients with Parkinson's disease: evidence from ideomotor apraxia testing. Issue 11 (November 1986) - Goldenberg, G; Wimmer, A; Auff, E; Schnaberth, G
Abstract : Compared with a group of age matched controls, patients with Parkinson's disease scored significantly lower in testing for ideomotor apraxia. Imitation of movement sequences was affected more severely than performance of single movements. The degree of impairment was not related to severity of motor disability, but correlated strongly with the results of tests that measured visuospatial and visuoperceptive abilities. It is suggested that defective encoding and central processing of visuospatial information impairs memory for movement which is necessary for correct imitation of movements. Enhanced vulnerability to interference between successively presented items may cause further deterioration of performance in the copying of movement sequences.